ANALISIS FAKTOR-FAKTOR YANG BERPENGURUH TERHADAP KAPASITAS FISKAL DAERAH KABUPATEN/KOTA DI INDONESIA PADA PERIODE 2019-2020 - Widi Dian Istiningsih; Andy Dwi Bayu Bawono (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Local government autonomy becomes independent in managing its authority. This can be seen from the strengthening of Fiscal Capacity or Regional Original Income. However, the purpose of implementing regional autonomy is to realize strong Regional Fiscal Capacity (KFD) in creating regional independence. This study aims to determine the effect of Regional Tax (PD), Regional Retribution (RD), Tax Revenue Sharing (BHP) and Gross Regional Domestic Product (GRDP) on Fiscal Capacity (KF). This study uses quantitative analysis techniques, and the method used in sampling in this study is purposive sampling. The number of samples collected is 998 districts/cities, there are 158 outlier data so that the number of samples used in this study is 840 districts/cities. The data that has been collected was analyzed using data analysis which first tested the classical assumptions before testing the hypothesis. Testing the hypothesis in this study using multiple regression analysis with t test, f test, and determinant coefficients. The results of this study indicate that Regional Tax (PD), Regional Retribution (RD), Tax Revenue Sharing (BHP) and Gross Regional Domestic Product (GRDP) have a significant effect on Fiscal Capacity (KF).